Award for Internal programs for Enhancing Teaching Excellence - Mavri, Aekaterini (My University, 2026)
Funded proposal through the Teaching Excellence Enhancement Program as an outstanding proposal and contribution to the educational community – IXN framework Implementation Manual
Keywords: Education